Invasive monitoring of blood pressure on stages of cerebral aneurysms endovasal coiling - Shevaga, Volodymyr; Netlyukh, Andriy; Kobyletsky, Oleg; Salo, Viktor (Ukrainian Neurosurgical Journal, 2015)
The purpose. To study haemodynamic changes in major cerebral arteries and in arterial aneurysm’s (AA) cavity on stages of endovascular embolization for prognosis of intraoperative complications and postoperative period course. Materials and methods. At the real time blood pressure (BP) in 44 patients was compared in internal carotid artery (ICA) and in AA cavity while performing endovascular coiling at subarachnoid hemorrhage, caused by AA rupture. Results. BP in a main artery during the surgery performing did not change substantially. Systolic BP changed on intermediate stages of embolization, BP changes were identified inside AA cavity. It was noted that in 43.2% patients systolic BP inside AA decreased and was about (30.7±9,1) mm Hg, in 56,8% increased by (27,6±4,7) mm Hg. After AA cavity embolization BP decreased in average on 7.7 mm Hg, thus BP correlation in AA cavity and ICA decreased from 87.3 to 77.9%. Conclusions. Invasive measurement of BP did not significantly affect duration of the surgery and was not accompanied by additional trauma. Hemodynamic parameters assessment in the artery and AA provided further information about the course and efficacy of endovascular neuroroentgenosurgical intervention, systolic BP increasing in AA cavity may indicate an increased risk of AA intraoperative rupture.